Trait Emotional Intelligence and School Burnout Discriminate Between High and Low Alexithymic Profiles: A Study With Female Adolescents - Farina, Eleonora; Pepe, Alessandro; Ornaghi, Veronica; Cavioni, Valeria (Frontiers in Psychology, 2021)
Alexithymic traits, which entail finding it difficult to recognize and describe one’s own emotions, are linked with poor trait emotional intelligence and difficulties in identifying and managing stressors. There is evidence that alexithymia may have detrimental consequences for well-being and health, beginning in adolescence. In this cross-sectional study, we investigated the prevalence and incidence of alexithymia in teenage girls, testing the statistical power of trait emotional intelligence (TEI) and student burnout to discriminate between high- and low-alexithymic subjects. A sample of 884 female high school students (mean age 16.2 years, age range: 14-19) attending three Italian academic-track high schools (social sciences and humanities curriculum) completed self-report measures of alexithymia, school burnout, and TEI. Main descriptive statistics and correlational analysis preceded the discriminant analysis. The mean alexithymia scores suggest a high prevalence of alexithymia in female adolescents; as expected, this trait was negatively correlated with TEI and positively associated with school burnout. Participants with high vs low alexithymia profiles were discriminated by a combination of TEI and burnout scores. High scores for the emotionality and self-control dimensions of TEI were strongly associated with membership of the low alexithymia group; high scores for the emotional exhaustion dimension of school burnout were indicative of membership of the high alexithymia group. These findings suggest crucial focuses for educational intervention: efforts to reduce the risk of emotional exhaustion and school burnout should especially concentrate on enhancing emotional awareness and self-control skills, both strongly associated with low levels of alexithymia.